Impact of left-behind duration on depression and anxiety in rural adolescents from mountainous areas and the moderating role of community resilience post-earthquake - Xiang, Yong; Yin, Hao; Yang, Jiaocan; Chen, Donghu; Zhang, Jingjing (Frontiers in Psychiatry, 2025)
IntroductionAdolescents in the mountainous regions of western Sichuan, China, are frequently exposed to earthquake disasters and often experience prolonged separation from parents due to labor migration. Previous studies have shown that both earthquake exposure and left-behind experiences negatively impact adolescent mental health, but the moderating role of community resilience remains underexplored.MethodsThis study conducted a cross-sectional survey in 2023 among 541 rural adolescents (aged 12–18) affected by the 2022 Luding earthquake. Standardized instruments — the Kutcher Adolescent Depression Scale (KADS-6), the Generalized Anxiety Disorder Scale (GAD-7), and the 10-item Conjoint Community Resiliency Assessment Measure (CCRAM-10) — were used to measure depression, anxiety, and perceived community resilience, respectively. Moderation analysis was conducted using Hayes' PROCESS macro (Model 1), with simple slopes and Johnson-Neyman techniques applied.ResultsThe duration of left-behind status was significantly and positively associated with depressive and anxiety symptoms. Perceived community resilience was negatively associated with these outcomes and moderated the relationship between left-behind duration and mental health. Specifically, higher levels of community resilience attenuated—but did not eliminate—the adverse effects of prolonged parental absence.DiscussionFindings highlight the dual burden of disaster exposure and family separation on adolescent mental health in rural mountainous settings. Community resilience, encompassing leadership, preparedness, trust, and social cohesion, offers partial buffering effects. The results underscore the need for targeted psychological interventions and community-based resilience building to protect vulnerable youth in disaster-affected areas.